The sale of wine within local food systems on the example of Italian law - Kapała, Anna (Przegląd Prawa Rolnego, 2019)
The purpose of the considerations is to determine in what forms under Italian law wine producers-farmers may sell wine directly to consumers it it meets the criteria of local food systems. In this respect, the regulations on direct sales, so-called “wine routes,” agro-tourism, and farmers’ markets, as well as the “agricultural products from zero kilometres” indications have been analysed. It has been established that Italian laws allow selling wine in all the forms of the short supply chains analysed in the study. Legal provisions in this respect govern farmers and the agricultural products they produce, both unprocessed and processed, including wine. What is more, there is a special instrument created to support the sale of wine in short supply chains – “wine routes” while the Law on Agritourism explicitly allows the serving of wine produced on a given farm. All these represent a form of implementing the idea of local food systems where the conditions such as close proximity between the place of production and the place of sale, direct or close social relationship between the producer and the consumer, the lack of intermediaries or the participation of only one intermediary, are satisfied.